ASSESSMENT OF KNOWLEDGE, ATTITUDE AND PRACTICE (KAP) OF BLOOD DONATION AMONG MBBS STUDENTS OF A MEDICAL COLLEGE IN KOLLAM, KERALA - Ahmad Nadeem Aslami; Abraham Jobby; Sony Simon; Nahla Nazarudeen; Pranav Raj; Mohammed Ramees; Nikhila Harigopal and Nishani N 8 (Journal of Evolution of Medical and Dental Sciences, 2015)
ABSTRACT: BACKGROUND: Blood transfusion is a very crucial component to manage patients suffering from various medical conditions. Voluntary blood donors are the need of the hour. There is a need to spread awareness among general population and students about blood donation to maintain a regular blood supply. Young medical students can serve as best example to take a lead in this noble cause. OBJECTIVE: To assess the Knowledge, Attitude and Practice (KAP) of Blood Donation among 1 st and 2 nd year MBBS students of a Medical College. MATERIAL AND METHODS: The cross sectional study was conducted in a medical college in Kollam district of Kerala in September 2013 among all 1 st and 2 nd year medical students. A separate Health awareness session was organized. Data was collected and analyzed with the Statistical Package of Social Sciences (SPSS) 12. RESULTS AND OBSERVATIONS: Not a single participant answered all knowledge questions correctly. Only 35% had adequate knowledge. The gender has no significant association with knowledge about blood donation. 90% of the respondents had a positive attitude about blood donation. Religion only plays a minor role in their decision to donate blood. Only 10% actually donated blood. 57% students gave blood to a needy relative. The most common reason for not donating blood was having no opportunity. There is a significant association between 2 nd year students and blood donation. After awareness session, the overall willingness to donate blood increased from 89.3% to 97.1%. CONCLUSION: Only one third of students have adequate knowledge level regarding blood donation. Only few among them have donated blood. Majority of them intend to donate blood in future. Information, Education and Communication (IEC) activities should be increased and regular seminars and classes should be conducted to increase awareness among medical students for encouraging them to donate blood voluntarily.